THE IMPACT OF FINANCIAL MANAGEMENT ON MSME SALES TURNOVER IN MARITENGNGAE DISTRICT, SIDENRENG RAPPANG REGENCY - Feby Sardini; Andi Sri Kumala Putri P; Usman Rahman (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the extent to which financial management influences the sales turnover of MSMEs in Kelurahan Pangkajene, Kecamatan Maritengngae, Kabupaten Sidenreng Rappang, particularly in the food and beverage subsector. MSMEs play a vital role in the local economy; however, many business owners have not yet implemented optimal financial management practices. A quantitative approach was employed using a survey method involving 67 MSME actors, and the data were analyzed using simple linear regression. The findings revealed that financial management has a significant influence on sales turnover, with a regression coefficient value of 0.784 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) was recorded at 0.569, indicating that 56.9% of the variation in sales turnover can be explained by financial management, while the remaining 43.1% is influenced by other factors. Thus, effective financial management has been proven to contribute significantly to increasing MSME sales turnover. It is crucial for business owners to improve their financial systems to achieve sustainable growth.